AST to Platelet Ratio Index (APRI), Fib-4 Score, and Pregnancy Outcome of Pregnant Women with Hepatitis B - Maghfirah, Desi; Yusuf, Fauzi; Abubakar, Azzaki; Rusly, Dewi Karlina; Darnifayanti, Darnifayanti (Faculty of Medicine, Universitas Padjadjaran, 2023)
Hepatitis B virus infection in pregnancy has become a major concern in many developing countries,. The relationship between hepatitis B virus infection and pregnancy is complex and puzzling. This study aimed to investigate the relationship between hepatitis B virus infection and pregnancy outcomes with the insights into the AST to Platelet Ratio Index (APRI) and Fib-4 score. This was a cross-sectional study on pregnant women with hepatitis B virus infections who underwent labor at dr. Zainal Abidin Hospital General Hospital, Aceh, Indonesia. Data were collected from the obstetric ward patient medical records from 2017 to 2019 and 77 pregnant women was identified to be infected with hepatitis B virus, of which 44 had complete medical record data and were included in the analysis. The median APRI in this study was 0.30 (0.1-1.2) while the median FIB-4 score was 0.74 (0.3-1.9). Delivery with live births was identified in 42 (95.5%) women. Term pregnancy and vaginal delivery were observed in 39 (88.6%) and 10 (22.7%) women, respectively, Complicated pregnancy was seen in 14 (31.8%) of pregnancies that included complications such as oligohydramnios, HELLP, severe preeclampsia, placenta previa, and premature rupture of membranes. APRI was higher in the stillbirth group (0.5 [0.2-0.8] p = 0.682) and preterm birth group (0.4 [0.2-0.6], p = 0.502). FIB-4 scores were higher in the stillbirth group (1.2 [0.5-1.8], p = 0.517) and preterm birth group (0.9 [0.4-1.9], p = 0.529). Hence, pregnancy does not always worsen liver function and is not related to the natural course of hepatitis B infection. Pregnancy with hepatitis B without fibrosis is not associated with poor pregnancy outcomes. Routine liver function examination is needed in pregnant mothers with hepatitis B virus infections.